Effect of Mother’s Discipline Parenting Pattern on Discipline Character of Kindergarten Children - Nia Kurniasih; Dwi Hastuti (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
This research aimed to analyze the effect of maternal discipline on discipline of children at two kindergarten in Bogor City. The research design used was a cross sectional study involving 46 mothers and children, selected by accidental sampling, and the data were collected using a questionnaire. Parenting discipline was measured using a questionnaire of The Dimensions of Discipline Inventory (DDI), which was adapted and modified from Straus and Fauchier (2011) with a Cronbach's alpha value of 0.864, and Character Development Questionnaire Preschooler adapted and modified from Hastuti (2014) with a Cronbach's alpha value of 0649. The results showed that there was a significantly positive correlation between the lenght of education and mother’s implementation of discipline, and there is a significantly positive correlation between marital status with cognitive appraisal of discipline. Cognitive appraisal of discipline is an opinion or judgment against parent parenting discipline either approved or not. Discipline of children was influenced by mother’s length of education, mother’s age, and situation in the application of discipline by mother (R2 Adjusted= 0.492). The situation in the application of discipline is a state or condition of the mother when applying disciplinary behavior to children.